Ethical Ideology and Ethical Judgments of Accounting Practitioners in Malaysia - Ismail, Suhaiza; Mohd Ghazali, Nazli A. (Gadjah Mada International Journal of Business, 2011)
The paper intends to explore the ethical ideology and ethical judgments of accounting practitioners in Malaysia. The objectives of this study are twofold. First, the paper intends to examine the factors that contribute to the different ethical ideology among Malaysian accounting practitioners. Second, it aims to investigate the influence of demographic factors and ethical ideology on ethical judgments of accounting practitioners. The study used Forsythâs (1980) Ethics Position Questionnaire instrument to examine the ethical ideology of the accountants and adopted ethics vignettes used by Emerson et al. (2007) to assess the ethical judgments of the respondents. From the statistical analysis, this study found that age and gender have a significant impact on ethical judgment but not on ethical ideology. In addition, idealism and relativism have a significant influence on ethical judgment, especially in a legally unethical situation.Â Â Â Â Â